2022
DOI: 10.2991/aebmr.k.220104.024
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Investment Among Economics and Business Students Based on Theory of Planned Behavior Framework

Abstract: Investment behavior has become a daily lifestyle of modern society. Financial investments are also growing to be an alternative, like stocks, bonds, mutual funds, foreign exchange even cryptocurrency. However, not all elements of society can accept this pattern of financial investment, even though technological advances have provided various facilities so that the public can make investment decisions anytime and anywhere. This study seeks to analyze the investment behavior of students who have finished their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…In line with previous research, the study demonstrates that subjective norms have no effect on behavioral intentions (Arias-oliva et al, 2019;Ayedh et al, 2020;Baur et al, 2015;Echchabi, Omar, et al, 2021;Mazambani & Mutambara, 2019;Nurbarani & Soepriyanto, 2022;Nurhayani et al, 2022;Zamzami, 2020). It is known that the influence and opinions of others have no effect on their intention to invest.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with previous research, the study demonstrates that subjective norms have no effect on behavioral intentions (Arias-oliva et al, 2019;Ayedh et al, 2020;Baur et al, 2015;Echchabi, Omar, et al, 2021;Mazambani & Mutambara, 2019;Nurbarani & Soepriyanto, 2022;Nurhayani et al, 2022;Zamzami, 2020). It is known that the influence and opinions of others have no effect on their intention to invest.…”
Section: Discussionsupporting
confidence: 89%
“…Multiple studies have produced contradictory findings regarding the relationship between subjective norms and behavior intentions. According to (Arias-oliva et al, 2019;Ayedh et al, 2020;Echchabi, Omar, et al, 2021;Mazambani & Mutambara, 2019;Nurbarani & Soepriyanto, 2022;Nurhayani et al, 2022;Zamzami, 2020), subjective norms do not influence an individual's intent to use cryptocurrencies. In contrast, (Almajali et al, 2022;Anser et al, 2020b;Echchabi, Aziz, et al, 2021; discovered that subjective norms influence behavioral intentions to use crypto.…”
Section: Relationship Between Subjective Norms and Behavioral Intentionmentioning
confidence: 99%
“…Several studies have produced conflicting findings regarding the relationship between subjective norms and behavioral intentions. Several studies have found that subjective norms have no effect on the intention to invest in cryptocurrency (Arias-oliva et al, 2019;Ayedh et al, 2020;Echchabi, Omar, et al, 2021;Mazambani & Mutambara, 2019;Nurbarani & Soepriyanto, 2022;Nurhayani et al, 2022;Zamzami, 2020). In contrast to these findings, other researchers discovered that subjective norms influence behavioral intentions to invest in cryptocurrency (Almajali et al, 2022;Anser et al, 2020;Echchabi, Aziz, et al, 2021;Pham et al, 2021).…”
Section: Relationship Between Subjective Norms and Behavioral Intenti...mentioning
confidence: 98%
“…Lada, S., et al, 2009 [109-110]). There are several theories that may be used to analyze the BI of cryptocurrency users UTAUT and UTAUT2 (Hasan, S. Z., et al, (2022)-Nurhayani, U., et al, (2022) [111] TPB [112]).…”
Section: Research Agendasmentioning
confidence: 99%